The role of Athena in fifth century Athenian drama - Sibley, Eleanor (1995)
The goddess Athena is currently perceived through a series of contradictions. She is both warrior and reconciler, killer and patron of the artisan, a goddess who denies her own womanhood and ignores the existence of women. Using Homer's Iliad and Odyssey and the extant complete plays of Aeschylus, Sophocles, Euripides and Aristophanes, this thesis reconciles each of these contradictions both within themselves and with each other. It finds that Athena had a prominent role as goddess of the polis: as a warrior she protected the polis from the external threat of war, and as a reconciler she protected it from the internal threat of civil strife. As polis goddess, Athena encourages peace and prosperity in her city; this requires that she inspire the artisan with techne, and the politician with wisdom. As polis goddess, Athena was also concerned for the perpetuation of her city and as such protected the children who were to be the future citizens, and the mothers who bore and nurtured them. This thesis argues that, as patron of techne, Athena becomes the patron of all women's work (which was all craft work). From this association the evidence of civic religion and the drama is used to argue for a relationship between Athena and Athenian women which was independent from Athenian men, independent from their relationship with Athena, and just as special.